Current Operative Management of Breast Cancer: An Age of Smaller Resections and Bigger Cures - Jack W. Rostas; Donna Lynn Dyess (International Journal of Breast Cancer)
Surgical resection was the first effective treatment for breast cancer and remains the most important treatment modality for curative intent. Refinements in operative techniques along with the use of adjuvant radiotherapy and advanced chemotherapeutic agents have facilitated increasingly focused breast cancer operations. Surgical management of breast cancer has shifted from extensive and highly morbid procedures, to the modern concept obtaining the best possible cosmetic result in tandem with the appropriate oncological resection. An ever-growing comprehension of breast cancer biology has led to substantial advances in molecular diagnosis and targeted therapies. An emerging frontier involves the breast cancer microenvironment, as a thorough understanding, while currently lacking, represents a critical opportunity for diagnosis and treatment. Collectively, these improvements will continue to push all therapeutic interventions, including operative, toward the goal of becoming more focused, targeted, and less morbid.